Atomic structure of PtCu nanoparticles in PtCu/C catalysts prepared by simultaneous and sequential deposition of components on carbon support. (May 2016) - Bugaev, L A; Srabionyan, V V; Pryadchenko, V V; Bugaev, A L; Avakyan, L A; Belenov, S V; Guterman, V E
Abstract: Nanocatalysts PtCu/C with different distribution of components in bimetallic PtCu nanoparticles (NPs) were synthesized by simultaneous and sequential deposition of Cu and Pt on carbon support. Electrochemical stability of the obtained samples PtCu/C was studied using the cyclic voltammetry. Characterization of atomic structure of as prepared PtCu NPs and obtained after acid treatment was performed by Pt L 3 - and Cu K -edge EXAFS using the technique for determining local structure parameters of the absorbing atom under strong correlations among them. EXAFS derived parameters were used for generation of structural models of PtCu NPs by the method of cluster simulations. Within this approach, the models of atomic structure of PtCu NPs obtained by the two methods of synthesis, before and after post treatment and after two months from their preparation were revealed.